2005
DOI: 10.1007/s00439-005-1340-x
|View full text |Cite
|
Sign up to set email alerts
|

Upstream stimulatory factor 1 associated with familial combined hyperlipidemia, LDL cholesterol, and triglycerides

Abstract: Positive evidence has been reported for linkage and association between the upstream stimulatory factor 1 gene (USF1) and familial combined hyperlipidemia (FCHL). We genotyped the two most positive single-nucleotide polymorphisms (SNPs) (usf1s1: rs3737787 and usf1s2: rs2073658) from previous studies in a large family sample. This sample included 2,195 subjects in 87 Utah pedigrees ascertained for early death due to coronary heart disease (CHD), early strokes, or early onset hypertension. There were a total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
61
6

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 37 publications
2
61
6
Order By: Relevance
“…The sex-specific differences, observed in the present analyses, are in accordance with several reports from the literature demonstrating sex-specific results for genetic variants within the USF1 gene and lipid markers (18,21,23), whereas in other studies, only men were analyzed (28,41). Also for the association between USF1 and cardiovascular disease and mortality, sex-specific results were found (42).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The sex-specific differences, observed in the present analyses, are in accordance with several reports from the literature demonstrating sex-specific results for genetic variants within the USF1 gene and lipid markers (18,21,23), whereas in other studies, only men were analyzed (28,41). Also for the association between USF1 and cardiovascular disease and mortality, sex-specific results were found (42).…”
Section: Discussionsupporting
confidence: 92%
“…In some studies (18,(21)(22)(23)(24), genetic variants within the USF1 gene showed associations with serum triglycerides, whereas in two US cohort studies of cardiovascular disease risk (25), in French Caucasians (26), and in Korean adults (27), no associations with serum triglycerides were observed.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Increased USF1 transactivation of its target genes has been suggested to explain the development of the metabolic syndrome [35,39], the dyslipidaemia associated with FCHL [36,40] and the development of diabetic complications [32,34]. Metabolic syndrome, type 2 diabetes and FCHL have all been linked to the USF1 gene [35][36][37]. A number of risk alleles of USF1 have been identified, which all represent variants of the non-coding sequence [36,38,41].…”
Section: Discussionmentioning
confidence: 99%
“…In liver as well as in other tissues, USFs play an important role in the regulation of genes by insulin [24][25][26] or glucose [30][31][32][33][34]. Interestingly, the USF1 gene on chromosome 1q21 has been linked with type 2 diabetes [35], FCHL [36,37] and both cardiovascular disease and all-cause mortality among women [38]. Allelic variants of USF1 may confer susceptibility to core features of the metabolic syndrome, such as glucose intolerance and dyslipidaemia [36,39,40].…”
Section: Introductionmentioning
confidence: 99%